Engenharia de resiliência (ER) em uma indústria de plásticos, aplicação do método de avaliação de sistemas de gestão de segurança e saúde no trabalho (MASST) - Kunrath, Igor Guilherme (2020)
Resilience engineering enables occupational health and safety management systems are evaluated using appropriate tools, guidelines, methods and procedures, overcoming challenges imposed by new technologies and adversities. In this context, the The objective of this dissertation was to apply the new Management Systems Assessment Method (MASST), as a case study in a medium-sized plastics industry, with emphasis on resilience engineering (RE) aspects. MASST was developed in a way comprehensive, using concepts such as the PDCA cycle, safety and health standards such as ISO 45.001 and elements of management systems, with the adoption of a management engineering approach resilience (RE). The application of MASST explored as sources of evidence the analysis of documentation, interviews and direct observation. The ER principles used in the new MASST were: learning, responsiveness, monitoring and anticipation, which Of the 140 requirements, 73 were aligned with ER. After applying the MASST, reports were developed with the strengths and opportunities for improvement, also with development of an action plan, with satisfactory results in relation to the objectives of the study, as identified in the systemic causes of the lack of safety and the priorities of actions. Among the limitations of applying the case study, it is highlighted that during the new coronavirus (COVID-19) pandemic. The need to communication and prior training before applying the MASST, examiners must have knowledge of RE concepts and principles, and also have solid knowledge in ergonomics.